2020
DOI: 10.2478/jvetres-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin C supplementation on the blood oxidative stress and antibody titre against Histophilus somni vaccination in calves

Abstract: IntroductionThe purpose of this study was to determine the effects of vitamin C supplementation on blood oxidative stress biomarkers and antibody response to vaccination in calves.Material and methodsThirty-four clinically healthy 2 week old Japanese Black calves were randomly assigned to two groups. Seventeen calves formed the VC group which received 1,000 mg of vitamin C daily from 2 to 8 weeks of age, and the other 17 calves of the control group did not receive supplementation. All calves received an inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is also of note that, to the best of our knowledge, despite stimulatory influence of vitamin C [63,64], selenium [65] and manganese [66] on antibody synthesis in humans and/or experimental animals, there is no studies on their influence on serological response to influenza virus vaccine. However, there are data indicating that they exert stimulatory influence on antibody response to some other vaccine, including (when selenium is in question) avian influenza virus in humans and/or experimental animals [67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…It is also of note that, to the best of our knowledge, despite stimulatory influence of vitamin C [63,64], selenium [65] and manganese [66] on antibody synthesis in humans and/or experimental animals, there is no studies on their influence on serological response to influenza virus vaccine. However, there are data indicating that they exert stimulatory influence on antibody response to some other vaccine, including (when selenium is in question) avian influenza virus in humans and/or experimental animals [67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the values recorded in human samples [ 13 ], in which the LOOH levels assessed using a ROMs test were 350 times higher than those obtained using a TOS assay, and far beyond the cytotoxicity threshold indicated in the literature [ 4 , 17 ]. At the same time, ROMs-assessed LOOH values in livestock species are remarkably lower than in humans [ 25 , 26 , 28 , 42 ], whereas TOS-assessed LOOH values do not greatly differ between livestock species and humans [ 43 , 44 , 45 , 46 ]. This discrepancy may be attributable to the higher CP oxidase activity in humans than in animal species [ 23 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against SARS-CoV-2 and the resultant activation of the immune system is likely to result in enhanced utilisation of immune supportive micronutrients, such as vitamin C. In cases of severe vitamin C deficiency, infants have been observed to go into shock following routine childhood vaccinations; rapid vitamin C administration was able to rescue many cases [ 64 , 65 ]. Animal studies have indicated that administration of vitamin C during vaccination or antigen challenge can stimulate an earlier and higher antibody response [ 66 , 67 , 68 ].…”
Section: Immunisation Supportmentioning
confidence: 99%